PENDIDIKAN DAMAI: Upaya Mencegah Budaya Anarkisme Pendidikan - Muh. Syamsuddin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The violence has hegemonied all aspects of human life as in the politics, economic, social, law and education. Hegemony in the education fild cause the dehumanization of the substance and the teaching methods. Educational methods developed during this time is a pedagogical approach or one direction that become a teacher as a perfect fiure (knows about much matter ) and the student as a object. This form is called the violence in education. This violence can result of split personality. This paper discusses the prevention of the violenceoccured in the education through peace education.